The matrix [videorecording (Blu-Ray)] - Wachowski, Lilly, 1967-; Wachowski, Lilly, 1967-; Wachowski, Lana, 1965-; Wachowski, Lana, 1965-; Reeves, Keanu; Fishburne, Laurence, III, 1961-; Moss, Carrie-Anne, 1970-; Weaving, Hugo, 1960- (Warner Bros. Entertainment, 2013)
When a computer hacker realizes the world is a hoax, an elaborate deception spun by machines of artificial intelligence, he is pulled into a fight to save humans from destruction.